Local Leaders’ Perception of Accountability in Service Delivery: A Case Study of Dar es Salaam City Council in Tanzania - Bujiku, Robert Renatus (Universiti Malaysia Sarawak (UNIMAS), 2019)
ABSTRACT This study is about local leaders’ perception of accountability in service delivery; the study has theoretical and methodological contribution in the field of accountability implementation practice in the context of developing countries, in particular, Dar es Salaam city council in Tanzania. While accountability is extensively discussed in the literature, there has been a very little work done, theoretically and methodologically on how individual local leader perceive accountability concept, and its implementation practice in service delivery at local governance level. Since accountability is a multi-dimensional and multidiscipline notion, yet there is inconsistency in literature regarding the meaning of accountability. The central focus of this study is to understand individual perceived meaning of accountability concept and its practice within Dar es Salaam city council in Tanzania, which has also not been comprehensively explored. When one considers the complexity and multi-dimensionality of the notion accountability, one also should question if local leaders comprehend the meaning of accountability as well as the effect of lack of accountability in social and public service delivery. Thus, this study aims to address these important theoretical and methodological gaps by providing a detailed case study of local leaders’ perception of accountability in Dar es Salaam city council. In achieving the expected qualitative results, data collection and analysis is done through well combined qualitative data tools, these include; observation, focus group discussion (FGD) and in-depth interview (IDI). Moreover, a total of 146 participants were purposively selected through snowball quota sampling from the five districts of Dar es Salaam city council; whereby 102 participants were selected to participate in FGDs, and 44 participants were selected to participate in IDIs so that to generate originality and trustworthiness of the empirical findings discussed in this research. The results obtained from this study indicate that there is misperception of accountability notion amongst local leaders in Dar es Salaam city council, as accountability is perceived as a process of implementing daily activities. Regardless of disharmony in defining accountability, such definitions by local leaders contradict the existing truth about accountability notion; scholars specify that the meaning of accountability is comprehensive when aspects of answerability, participation, transparency, and controllability are well articulated in understanding the concept. Since local leaders in Dar es Salaam were not aware with those specified aspect of accountability meaning, their misperception appeared to accelerate lack of accountability across the Dar es Salaam local governments. Thus, in order to have effective implementation of accountability at local level, the study recommends soundable comprehensive accountability training programs to local leaders so that to equip them with knowledge and skills about accountability notion and its practice in service delivery. Besides, the study suggests to policy makers and other local stakeholders to think about overhauling, and restructuring accountability system in Dar es Salaam city council so that to enhance accountability practice. Keywords: Accountability, perception, service delivery, local leaders, Dar es Salaam